Eksplorasi Perspektif Mahasiswa dalam Penggunaan Turnitin untuk Menghindari Plagiasi - Yushinta Prassanty Antoroputri; Diah Priharsari; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In the world of education, artificial intelligence (AI) plays a role in conveying various information and also makes the learning process of teachers and students more efficient. Intellectual crime in the form of plagiarism seems to have become a common phenomenon in education and in society. There are many motives behind this despicable act. The causes of such intellectual crimes are also very complex. Technological advances, in addition to triggering the growth and development of plagiarism activities, also provide a means to detect plagiarism activities through plagiarism detection tools or software. The number of cases of plagiarism in universities, finally applying technology to reduce the number of student plagiarism by using the plagiarism checker application. As an application, Turnitin is widely used by universities around the world, especially to check the authenticity or originality of a work. Therefore, this study aims to determine the understanding and perspective of students related to plagiarism and the use of Turnitin for plagiarism detection. Data collection research conducted by qualitative methods of case study approach using semi-structured interview techniques and will focus on extracting problems in students of the Faculty of Computer Science, University of Brawijaya. Then the data that has been obtained will be analyzed using thematic analysis stages. The findings of this study resulted in fact data consisting of two main themes, namely the understanding of plagiarism and turnitin with 9 categories and 29 codes.